2018
DOI: 10.1038/s41418-018-0059-x
|View full text |Cite
|
Sign up to set email alerts
|

Cripto-1 contributes to stemness in hepatocellular carcinoma by stabilizing Dishevelled-3 and activating Wnt/β-catenin pathway

Abstract: Identification and characterization of functional molecular targets conferring stemness properties in hepatocellular carcinoma (HCC) offers crucial insights to overcome the major hurdles of tumor recurrence, metastasis and chemoresistance in clinical management. In the current study, we investigated the significance of Cripto-1 in contributing to HCC stemness. Cripto-1 was upregulated in the sorafenib-resistant clones derived from HCC cell lines and patient-derived xenograft that we previously developed, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 55 publications
2
49
0
Order By: Relevance
“…Global gene expression profiles by whole‐transcriptome sequencing (WTS) and clinicopathological parameters of the cancer genome atlas (TCGA) dataset were obtained from TCGA data portal and http://firebrowse.org (Broad Institute). Data on 50 paired HCC and nontumoral liver samples were retrieved for analysis and subsequent differential gene expression analysis was performed as we previously described . Differential gene expression analysis was carried out by means of edgeR on the raw read counts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Global gene expression profiles by whole‐transcriptome sequencing (WTS) and clinicopathological parameters of the cancer genome atlas (TCGA) dataset were obtained from TCGA data portal and http://firebrowse.org (Broad Institute). Data on 50 paired HCC and nontumoral liver samples were retrieved for analysis and subsequent differential gene expression analysis was performed as we previously described . Differential gene expression analysis was carried out by means of edgeR on the raw read counts.…”
Section: Methodsmentioning
confidence: 99%
“…The assay was performed as we previously described. 20,21 Five hundred HCC cells, unless otherwise specified, were suspended in DMEM/F12 GlutaMAX™ medium (Invitrogen, Carlsbad, CA) supplemented with B27 (Invitrogen, Carlsbad, CA), 4 μg/ml insulin (Sigma-Aldrich), 20 ng/ml of epidermal growth factor (Sigma-Aldrich), 20 ng/ml of basic fibroblast growth factor (Sigma-Aldrich, St. Louis, MO) were seeded onto a 24-well plate, coated with 1% polyHEMA (Sigma-Aldrich, St. Louis, MO) for 8-10 days. Subsequently, the tumorspheres were photographed under the light microscope and the total number of spheres formed was counted.…”
Section: Tumorsphere Formation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In hepatocellular carcinoma (HCC), it was shown that Cripto promotes stemness by stabilizing Dishevelled-3 and activating the Wnt/β-catenin signaling cascade. The knock down of Cripto also reduced the activity of components of the Wnt/β-catenin pathway, such as β-catenin, AXIN2, and C-MYC [90]. The invasion potential of HCC cells has been shown to be regulated by NANOG, which increased the expression of Nodal and Cripto to promote SMAD3 phosphorylation and SNAIL expression and EMT progression [91].…”
Section: Cripto In Oncologymentioning
confidence: 99%
“…Enhanced expression of several CSC-related markers, such as epithelial cell adhesion molecule (EpCAM), CD44, CD133, and Nanog, is associated with poor prognosis of HCC [ 4 – 7 ]. Similarly, alterations in stemness-related signaling pathways, such as Wnt/β-catenin, Notch, and Hedgehog pathways, resulted in chemoresistance and recurrence of HCC [ 8 – 10 ]. Therefore, CSCs and their associated pathways are becoming the focus of potential therapies for HCC.…”
Section: Introductionmentioning
confidence: 99%